L’AMOUR ENTÉNÈBRE - Jean-Jacques SARFATI (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
The Darkness of Love. This text defends the idea of the philosophical evil as opposed to purely psychological and/or sociological evil. Philosophical evil is an evil that forces action and reflection in all matters. Love, in the contemporary world, is a victim of this evil and it has been plunged into darkness by mediatizing approaches that drive us to despair. The objective here is to give substance to the concept of love by enlightening it again and taking it out of the vision that is either too relativist or too absolutist in which it has been confined.